Health Auditing and Administration Using IoT with the Help of Cloud - Tripathi, Raghvendra Narain (Indian Journal of Computer Science, 2021)
One of the biggest applications created with the Internet of Things (IoT) is advanced online health administration system. Using sensors which are worn or are either present in networks gives huge amount of data which are related to the physiological health of consumers. By collecting and analysing this information, one can meet big challenges in the domain of health care system. With the help of this amount of information and processing techniques, we can bring some of the biggest changes in the domain of health administration system such as (a) With these techniques and information we can replace the post disease treatment with pre-disease treatment (b) It can also help in making personal profile of patients and so, profile treatment which is required by patients can be done. (c) It also helps in minimizing the operating cost while maximizing the output of the health administration system. This paper shows the convenience and risks associated with the use of IoT for achieving the dream of the advanced health administration system.